Mathematical modelling for hydrogen production from steam gasification of cellulose - Inayat, A. (Trans Tech Publications Ltd, 2014)
In Malaysia, due to its abundance, oil palm is a good candidate to be used as a feedstock for hydrogen production. Oil palm biomass generally consists of cellulose, hemicellulose and lignin. Steam gasification, coupled with CO2 removal has been shown to be one of the promising methods for hydrogen production. This work focuses on the mathematical modeling of hydrogen production from cellulose via steam gasification and steam gasification with in-situ CO2 capture using CaO. The results are compared and rationalized against published data on steam gasification of pure cellulose and good agreement is observed. The model predicts an increase in hydrogen output from 48 to 56 mol with the addition of CaO into the system. By increasing temperature and steam/biomass ratio the cold gas efficiency decreases, however, temperature have higher impact compared to steam/biomass ratio. Â© 2014 Trans Tech Publications, Switzerland.